Patterns of pulmonary function and mortality in chronic heart failure, results from the MyoVasc study. (14th October 2021) - Heidorn, M; Mueller, F; Schuch, A; Buch, G; Velmeden, D; Soehne, J; Troebs, S.O; Schulz, A; Strauch, K; Schmidtmann, I; Lackner, K.J; Gori, T; et al.
Abstract: Background: Preclinical evidence suggests that pulmonary fibrosis due to left heart disease may represent end-organ damage in heart failure (HF). Vice versa, decreased pulmonary function is related to worsening of heart failure in the absence of obstructive airway pattern. Purpose: This study investigated the relationship between patterns of pulmonary function (i.e. obstruction and restriction) and mortality in chronic HF. Methods: For the present analysis data from the MyoVasc-study (N=3, 289) were analysed. During a five-hour examination in the dedicated study center, systematic phenotyping was performed in a highly standardized setting. Chronic HF was defined as American Heart Association HF Stage C/D. Information on pulmonary function was assessed via body plethysmography (MasterScreen Body, Carefusion, Germany). Participants with forced expiratory ratio <0.7 or COPD were categorized as obstructive, while restriction was defined as reduction in total lung capacity. Information on vital status was obtained via registration offices. Results: The analysis sample comprised 1, 509 individuals with chronic heart failure and information on pulmonary function, of whom 286 had HF with reduced ejection fraction (HFrEF), 559 HF with preserved ejection fraction (HFpEF), and 333 HFpEFborderline. The mean age was 64.6±11.3 years, 38.7% were female. In the sample 124 subjects had pulmonary restriction and 400 individuals had an obstruction. During a median time to follow up of 3.70 (inter quartile range 1.25 to 4.00) years, death occurred in 170 individuals. Among clusters of pulmonary function most participants died in the restriction group (25.0%), followed by pulmonary obstruction (12.2%) and normal pulmonary function (7.3%, P for trend <0.001). Cox- regression analysis adjusted for age, sex and height revealed pulmonary restriction (hazard ratio (HR) 3.00 [95% confidence interval 2.04–4.42], P<0.001] and obstruction (HR 1.61 [1.11–2.35], P=0.01) as predictors of all-cause death. After additional controlling for traditional cardiovascular risk factors and the clinical profile only pulmonary restriction remained an independent predictor of mortality (HRrestriction 2.12 [1.50–3.43]; P=0.002; HRobstruction 1.35 [0.91–2.00]; P=0.10). Among HF phenotypes obstruction was only in individuals with HFpEF an independent predictor of all-cause death (HRHFpEF 2.60 [1.29–5.23]; P=0.007; HRHFpEFborderline 1.58 [0.70–3.57]; P=0.27; HRHFrEF 0.96 [0.52–1.78]; P=0.90), while pulmonary restriction was found to be predictive for death only in subjects with HFpEFborderline (HRHFpEF 2.15 [0.70–6.64]; P=0.18; HRHFpEFborderline: HR 5.47 [2.56–11.68]; P<0.001; HRHFrEF 1.74 [0.88–3.46]; P=0.11) Conclusion: In chronic heart failure, pulmonary restriction was a stronger predictor of mortality than obstructive airway pattern. The present analysis supports the hypothesis of pulmonary fibrosis as end-organ damage in HF, and may potentially represent a therapeutic target. Funding Acknowledgement: Type of funding sources: Public Institution(s). Main funding source(s): German Center for Cardiovascular Research (DZHK)